Completion of Tricin Biosynthesis Pathway in Rice: Cytochrome P450 75B4 Is a Unique Chrysoeriol 5′-Hydroxylase. Issue 4 (16th June 2015) - Lam, Pui Ying; Liu, Hongjia; Lo, Clive
Abstract : Biosynthesis of tricin requires specific hydroxylation catalyzed by a phylogenetically distinct hydroxylase. Abstract: Flavones are ubiquitously accumulated in land plants, but their biosynthesis in monocots remained largely elusive until recent years. Recently, we demonstrated that the rice ( Oryza sativa ) cytochrome P450 enzymes CYP93G1 and CYP93G2 channel flavanones en route to flavone O -linked conjugates and C -glycosides, respectively. In tricin, the 3′, 5′-dimethoxyflavone nucleus is formed before O -linked conjugations. Previously, flavonoid 3′, 5′-hydroxylases belonging to the CYP75A subfamily were believed to generate tricetin from apigenin for 3′, 5′- O -methylation to form tricin. However, we report here that CYP75B4 a unique flavonoid B-ring hydroxylase indispensable for tricin formation in rice. A CYP75B4 knockout mutant is tricin deficient, with unusual accumulation of chrysoeriol (a 3′-methoxylated flavone). CYP75B4 functions as a bona fide flavonoid 3′-hydroxylase by restoring the accumulation of 3′-hydroxylated flavonoids in Arabidopsis ( Arabidopsis thaliana ) transparent testa7 mutants and catalyzing in vitro 3′-hydroxylation of different flavonoids. In addition, overexpression of both CYP75B4 and CYP93G1 (a flavone synthase II) in Arabidopsis resulted in tricin accumulation. Specific 5′-hydroxylation of chrysoeriol to selgin by CYP75B4 was further demonstrated in vitro. The reaction steps leading to tricin biosynthesis are then reconstructed as naringenin → apigenin → luteolin → chrysoeriol → selgin → tricin. Hence, chrysoeriol, instead of tricetin, is an intermediate in tricin biosynthesis. CYP75B4 homologous sequences are highly conserved in Poaceae, and they are phylogenetically distinct from the canonical CYP75B flavonoid 3′-hydroxylase sequences. Recruitment of chrysoeriol-specific 5′-hydroxylase activity by an ancestral CYP75B sequence may represent a key event leading to the prevalence of tricin-derived metabolites in grasses and other monocots today.